Establishing the concept of Muslim friendly hotel in Malaysia - Wan Zulkifli, Wan Sahida (2014)
This thesis examines the basic concept of Muslim friendly hotel from the view of key stakeholders in Malaysia include policy makers and hotel practitioners. It aims to understand the concept of Muslim friendly hotel and identify the characteristics of Muslim-friendly services and facilities from the key stakeholder’s point of view. A qualitative study using a case study approach was conducted with the aim to understand on the concept of Muslim friendly hotel in Malaysia, due to limited literature and sources in this field of study. In this thesis, a case study was adopted for the exploratory study. Several cases were examined to understand their similarities and differences. Non-participant observation was conducted in selected hotels to identify the facilities and services offered. A total of 8 in-depth interviews were conducted on relevant local authority’s bodies, ministries and selected hotel practitioners in Malaysia in order to obtain a clear view on Muslim friendly hotel. The interviews were tape recorded, transcribed and coded into raising themes. The study identified 10 themes on the concept of Muslim friendly hotel in Malaysia. The findings showed that providing Halal food and beverage, prayer facilities, Islamic design and decoration, Islamic programs, segregation of facilities between men and women, safety and security, Muslim employees, Islamic floor, appropriate dress code for employee and finance practice accordance to Islamic principles were the major themes for the concept of Muslim friendly hotel. From the themes emerged the researcher categorized it into four main theme; that are operation, services, environment and finance theme. Besides, the policy maker also stressed Muslim friendly hotels should undertake activities compliant to Islamic principles such as provide separate facilities between men and women in the hotel in order to cater the needs for Muslim guests. In addition, hotel practitioners also mention providing Halal food and beverage, and providing Muslim-friendly services and facilities were the most important in developing the concept of Muslim friendly hotel. Views from stakeholders are crucial in order to develop the basic concept of Muslim friendly hotel in Malaysia and also to develop the standard guidelines in Malaysian tourism industry.